Hemodialysis Experience of a Large Group of Syrian Refugees in Turkey: All Patients Deserve Effective Treatment - Meltem Gursu; Mustafa Arici; Kenan Ates; Rumeyza Kazancioglu; Pinar Guneser Yavas; Murat Ozturk; Bulent Altun; Turgay Arinsoy (Karger Publishers, 2019)
Background/Aims: Refugee dialysis is a worldwide growing dilemma with limited experience. This report presents the largest hemodialysis (HD) patient registry data of Syrian refugees in Turkey. Methods: Demographic, clinical, laboratory, and dialysis practice data of 345 Syrian HD patients during one year were collected and analyzed. Results: There were 345 prevalent Syrian HD patients at the end of 2016. Majority of the patients were placed in the Southeast Anatolian Region. The majority of the patients (74.8%) are in the age range of 20-64 years. Dialysis vintage in Turkey is less than 12 months in 20.8% and less than one month in 29.3% of patients. The vascular access was arteriovenous fistula in the majority of patients (72.5%). Kt/V is over 1.7 in 57%, serum albumin is above 35 g/L in 65.8% and hemoglobin level is more than 100 g/L in %65.2 of the patients. The ratio of patients with serum phosphorus level of 1.13-1.77 mmol/L was 56.2%. Twenty Syrian HD patients (14 male, 6 female) died within the year 2016 and annual mortality rate was 5.7%. Conclusion: This study with the largest number of Syrian refugees undergoing maintenance hemodialysis showed good dialysis practices, acceptable values for dialysis adequacy and biochemical parameters along with lower mortality compared to native HD population of Turkey. Longer follow up will enrich the knowledge related to care of refugee population in all over the world.